Unveiling Another Missing Piece in EBV-Driven Lymphomagenesis: EBV-Encoded MicroRNAs Expression in EBER-Negative Burkitt Lymphoma Cases - Mundo, Lucia; Ambrosio, Maria R.; Picciolini, Matteo; Lo Bello, Giuseppe; Gazaneo, Sara; Del Porro, Leonardo; Lazzi, Stefano; Navari, Mohsen; Onyango, Noel; Granai, Massimo; Bellan, Cristiana; De Falco, Giulia; et al. (Frontiers in Microbiology, 2017)
Epstein–Barr virus (EBV) is a gammaherpesvirus linked to a number of lymphoid and epithelial malignancies, including Burkitt lymphoma (BL) in which its frequency ranges from 30% in sporadic cases to 100% in the endemic ones. The possible contribution of EBV to BL pathogenesis is largely unknown. It has been suggested that EBV may be associated with all of the cases, including those diagnosed as EBV negative by a mechanism of hit-and-run. Early during oncogenesis, viral genes are essential for initiating disease. Progressively, viral genome is lost to escape the immune system and host mutations accumulate in proto-oncogenic cell. The main problem with the hit-and-run hypothesis is the lack of evidence in primary tumors. The routine methods applied to detect the virus [i.e., immunohistochemistry and EBV-encoded RNAs (EBER) in situ hybridization (ISH)] have a low specificity and accuracy. The aim of this study was to identify the most suitable method to detect EBV infection in pathology samples by applying conventional and non-conventional methods (i.e., EBV-microRNAs detection and EBV viral load measurement). We investigated a total of 10 cases and we found that all the samples (n = 6) diagnosed as EBV negative by immunohistochemistry and EBER-ISH demonstrated the presence of EBV-microRNAs and EBV genome. This points at the possibility that EBV might have contributed to lymphomagenesis in all our patients, and propose microRNAs detection as the most specific and sensitive tool to recognize EBV vestiges. It is worth noting that our data would have considerable implications for EBV-related diseases control. By using anti-EBV vaccines, one could potentially prevent also some cancers less suspected of a viral origin because of viral genome loss.